Núcleo vegetal en la reinterpretación de la arquitectura biomimética en un centro de investigación en biotecnología alimentaria en Cali del Valle de la Cauca. (2022)
Biomimetic architecture, biomimicry or biomimicry, are a series of terms that are currently being used to refer to architecture designed from nature, which seeks sustainable solutions for buildings by adapting architecture to nature. However, this topic of architecture has generated various points of debate where biomimicry opens into two main branches: nature as a source of inspiration and mimicry with nature. The biomimicry principle is fundamental for the improvement of the agro-industrial sector since it allows generating a harmony between the technological, nature and sustainability that helps to technify the sector in Cali, but always starting from the natural, in order to create suitable spaces for the research in biotechnology that are open to the city, this given that the country currently lags behind in the technology sector applied to the food industry, making producers unable to compete in a sector both local and international.